Hubungan Pelaksanaan Program Pengelolaan Penyakit Kronis (Prolanis) Terhadap Kepuasan Peserta Di Puskesmas Maiwa Kabupaten Enrekang - Rosdiana, Rosdiana; Ramlan, Pratiwi; Adri, Khaeriyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
The Chronic Disease Management Program (Prolanis) addresses health problems related to non-communicable diseases. Maiwa Health Center showed an increase in both targets and assistance after the implementation of Prolanis. This study aims to examine the relationship between the implementation of a chronic disease management program (prolanis) and participant satisfaction at the Maiwa Community Health Center. This research uses quantitative methodology with a cross-sectional design. The population of this study consisted of all Prolanis participants diagnosed with hypertension and diabetes mellitus, totaling 166 people. This research uses a data collection approach such as observation, interviews, surveys and questionnaires. This research uses data analysis techniques which include validation tests, reliability tests, and chi-square tests. The findings of this research show that health consultation activities, home visits, and SMS gateway reminders produce a p value of 0.001 (p < 0.005), physical activity provides a p value of 0.004 (p < 0.005), while group education and health status monitoring show a p value of 0.002 (p < 0.05).